Koalisi Kompromistis Berbasis Kepentingan dalam Integrasi Sistem Pemerintahan Presidensial dan Multi Partai - Mahardika, Ahmad Gelora (Jurnal Review Politik, 2019)
Since the reform era, Indonesia has implemented a presidential government system combined with a multi-party system. The consequence of this system is that political parties are forced to make coalitions with other political parties. Whereas the coalition is usually applied in a country that adheres to a parliamentary system of government, this is because in a parliamentary system, the parliament has the power to dismiss the President or Prime Minister from his position as head of government. Meanwhile in a country with a presidential system, the coalition actually held the President hostage to political interests and was forced to compromise with the supporting political parties. Issues that later arose, the coalition built through the integration of these two systems was not based on similar ideology or vision and mission, but was based on pragmatic political interests. Therefore this article tries to prove this hypothesis by using comparative studies in other countries that apply concepts similar to those in Indonesia, namely Brazil, Bolivia and Chile.